If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying g = 3f + 13 Reorder the terms: g = 13 + 3f Solving g = 13 + 3f Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Simplifying g = 13 + 3f
| -(x-2)+3x=-3(x+4)+15 | | 6=-3+36 | | 41=-5x+6 | | 6+6n=-2-2n | | x=6y+11 | | t^3-3t^2+3t-2=0 | | 4(v+2)-11=9 | | 5x+8y=775 | | 3.5+y=1.05 | | (7p-8)(8p+9)=0 | | 2(v-5)-15=-3 | | 10+4y=8 | | 6-3x+2(4x-5)=12+2x-(4x+3) | | x+4-11= | | y+.2=.6(y+3) | | 2(x-2)=10x+4 | | j^2=144 | | 3(u+1)=18 | | k^2=100 | | -2(k-8)=0 | | 3(2y+1)=9 | | q^2=121 | | F(x)=2x^2+36x-7 | | i*z^2+(3+i)z+2-2i=0 | | p^2=1 | | 10g-6=-8g | | 30-26=4-5x | | 8p-15=57 | | k^2=64 | | 2(m-5)+6=2m+16 | | y=3-2*(-2) | | 2(m-5)+6=2m-4 |